Advances in 177Lu-PSMA and 225Ac-PSMA Radionuclide Therapy for Metastatic Castration-Resistant Prostate Cancer - Sui Wai Ling; Erik de Blois; Eline Hooijman; Astrid van der Veldt; Tessa Brabander (MDPI AG, 2022)
For patients with metastatic castration-resistant prostate cancer (mCRPC), the survival benefit of classic treatment options with chemotherapy and drugs targeting androgen signaling is limited. Therefore, beta and alpha radionuclide therapy (RNT) have emerged as novel treatment options for patients with mCRPC. Radioligands target the prostate-specific membrane antigen (PSMA) epitopes, which are upregulated up to a thousand times more in prostate cancer cells compared to the cells in normal tissues. For this reason, PSMA is an excellent target for both imaging and therapy. Over the past years, many studies have investigated the treatment effects of lutetium-177 labeled PSMA (177Lu-PSMA) and actinium-225 labeled PSMA (225Ac-PSMA) RNT in patients with mCRPC. While promising results have been achieved, this field is still in development. In this review, we have summarized and discussed the clinical data of 177Lu-PSMA and 225Ac-PSMA RNT in patients with mCRPC.